The effect of N-3 fatty acid (fish oil) supplementation on plasma lipoprotein and arterial lipids in Vervet monkeys (Cercopithecus aethiops) with established atherosclerosis - Smuts, Cornelius Mattheus (Stellenbosch : Stellenbosch University, 2012)
Dissertation (Ph. D.) -- University of Stellenbosch, 1996.